Discovering the essence of scientific literacy: A historical–grammatical hermeneutic analysis of contextual learning in science education - Sakul, Raymond Andrew; Fobia, Paulus; Pane, Exson Eduaman (Universitas Islam Negeri Raden Intan Lampung, 2025)
Contextual learning in science education deeply engages students by connecting scientific concepts to real-life experiences, enhancing motivation, meaningful understanding, retention, and problem-solving skills. Kyza & Georgiou's meta-analysis and the findings of Bennett et al. demonstrate its effectiveness. However, the ontological and epistemological meanings of scientific literacy, which are intended to be developed through this approach, remain underexplored. This study aims to investigate the meaning of literacy, science, and truth in the context of science education through a historical-grammatical hermeneutic approach. This study uses a qualitative hermeneutic method that integrates a historical analysis of the development of scientific literacy from positivism to constructivism and humanism and a grammatical study of key terms such as literacy, science, context, and learning in educational policies and curriculum frameworks. The interpretation process is carried out circularly to understand the meaning within the social and pedagogical context. The results show that scientific literacy extends beyond understanding scientific texts to encompass the ability to connect scientific knowledge with human responsibility, socio-scientific issues, and ecological awareness. Contextual learning is an effective pedagogical bridge for fostering meaningful scientific literacy by connecting scientific concepts with real-life experiences and student reflection.